2019
DOI: 10.1111/isj.12237
|View full text |Cite
|
Sign up to set email alerts
|

Trust in sharing encounters among millennials

Abstract: The sharing economy is a defining feature of the millennial generation. We report on a study of 1047 millennials and find that trust has more of an impact on their willingness to engage in some sharing encounters than in others. In particular, trust matters more in high-dimensionality sharing encounters-those encounters that have a longer duration, require a greater financial investment, involve more social interaction, etc. Further, it is important to note that all sharing encounters take place through two-si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 164 publications
(331 reference statements)
1
33
0
5
Order By: Relevance
“…First, offline collaborative consumption networks are more socially complex than currently reflected in existing online-only research. Typically, research on online market platforms and platform economics restrict the scope of involved actors to supply, demand, and an intermediary (Constantiou, Marton, & Tuunainen, 2017) to investigate how factors like price (Zimmermann et al, 2018) or trust (Mittendorf et al, 2019) affect collaborative consumption behaviour. However, collaborative consumption networks involve additional actors that provide essential complementary services to the platform model.…”
Section: Intensified Product Usementioning
confidence: 99%
See 1 more Smart Citation
“…First, offline collaborative consumption networks are more socially complex than currently reflected in existing online-only research. Typically, research on online market platforms and platform economics restrict the scope of involved actors to supply, demand, and an intermediary (Constantiou, Marton, & Tuunainen, 2017) to investigate how factors like price (Zimmermann et al, 2018) or trust (Mittendorf et al, 2019) affect collaborative consumption behaviour. However, collaborative consumption networks involve additional actors that provide essential complementary services to the platform model.…”
Section: Intensified Product Usementioning
confidence: 99%
“…However, our review showed that platform research on intensified product use beyond a purely economic motive is scarce (Achachlouei et al, 2015; Achachlouei & Moberg, 2015; Cohen & Muñoz, 2016; King, Burgess, Ijomah, & McMahon, 2006; Vykoukal, Wolf, & Beck, 2009). Most IS research on collaborative consumption and the sharing economy refers to sustainability only indirectly or spuriously, if at all (Greenwood & Wattal, 2017; Guo, Li, & Zeng, 2019; Mittendorf, Berente, & Holten, 2019; Teubner & Flath, 2019; Weber, 2014, 2016, 2017; Zimmermann, Angerer, Provin, & Nault, 2018). Future research could leverage current knowledge on platforms to better understand how digital platforms enable intensified product use to improve both economic and environmental sustainability.…”
Section: Mobilising Is Scholarship For a Cementioning
confidence: 99%
“…(driver and co-passenger/s), which is a non-recurring relationship based on digital and real-time interactions (Mittendorf, Berente, & Holten, 2019). Trust can also reduce the perceived risk of service sharing (Lamberton & Rose, 2012).…”
Section: Research Model and Hypotheses Developmentmentioning
confidence: 99%
“…In the fifth paper, Christoph Mittendorff, Nicholas Berente, and Roland Holten () explore the sharing economy from the perspective of millenials. They report on a study of 1047 millennials and find that trust has more of an impact on their willingness to engage in sharing encounters that have a longer duration, require a greater financial investment and involve more social interaction.…”
Section: Acknowledgementmentioning
confidence: 99%